The impact of hip rotator strength training on agility in male high school soccer players - Nelson, J.; DeBeliso, M. (The Sport Journal, 2014)
The strength of the muscles surrounding a joint contributes to the stability of the joint. The stability of a joint provides the foundation for large muscle groups to perform high speed forceful actions. The purpose of this study was to examine if strengthening of the hip rotator muscles could improve measures of agility. Twenty-nine male high school soccer players were recruited to participate in a 9-week matched pair study. The control and the experimental group participated in regular weight training and soccer practice. Additionally, the experimental group performed three sets of the hip rotator exercises using latex chords (medial and lateral rotation) twice per week with both legs. The dependent variables were the T-Test, the Hexagon Test, and the 20-Yard Shuttle Run. All athletes were pre- and post-tested on each of the agility drills. A gain score was then calculated as the difference between pre- and post-test agility scores. An independent t-test was used to determine if there were any differences (p < 0.05) between the experimental and control groups. Statistical analysis showed no significant difference between the two groups for T-test (p=0.12), Hexagon test (p=0.35), and 20-yard shuttle run (p=0.18). The research hypothesis, which stated that adding hip strengthening exercises for the experimental group would produce faster times on the agility tests, was rejected. Possibly the volume of training, which often included three hours of exercise and practice per day, rendered the additional hip strengthening exercises insignificant. Repeating the experiment in the off-season with lower training volume might produce different results.